2021
DOI: 10.1039/d1ma00727k
|View full text |Cite
|
Sign up to set email alerts
|

Construction of chemical self-charging zinc ion batteries based on defect coupled nitrogen modulation of zinc manganite vertical graphene arrays

Abstract: The self-charging power systems, which can simultaneously achieve energy harvesting and storage, play a significant role in the field of energy technology. Nevertheless, the traditional integrated systems are not only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…After removing basic zinc sulfates, the discharge capacity of a Zn/BQPH battery can be recovered to its initial level (Figure S34). Impressively, our air-rechargeable Zn/BQPH battery shows a superior electrochemical performance in comparison with other previously reported cases of air-rechargeable AZBs (Figure e). ,,, In addition, the discharge process of the Zn/BQPH battery in an open air environment can be accompanied by the air-charging behavior. The Zn/BQPH battery displays a high initial discharge specific capacity of 1076 mAh g –1 at 0.1 A g –1 in an open air environment, which is much higher than that (413 mAh g –1 ) in a sealed Ar environment (Figure S35).…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…After removing basic zinc sulfates, the discharge capacity of a Zn/BQPH battery can be recovered to its initial level (Figure S34). Impressively, our air-rechargeable Zn/BQPH battery shows a superior electrochemical performance in comparison with other previously reported cases of air-rechargeable AZBs (Figure e). ,,, In addition, the discharge process of the Zn/BQPH battery in an open air environment can be accompanied by the air-charging behavior. The Zn/BQPH battery displays a high initial discharge specific capacity of 1076 mAh g –1 at 0.1 A g –1 in an open air environment, which is much higher than that (413 mAh g –1 ) in a sealed Ar environment (Figure S35).…”
Section: Resultssupporting
confidence: 45%
“…This is also reflected by the discharge capacity of the Zn/BQPH battery during the air-charging process. The Zn/BQPH battery delivers a discharge capacity of 128 mAh g –1 after oxidation for only 4 h. When the air-charging time reaches 10 h, the Zn/BQPH battery exhibits a high discharge capacity of 351 mAh g –1 (Figure b), which is higher than the cases of previously reported air-rechargeable AZBs. ,,, However, the discharge capacity of Zn/BQPH batteries degrades when the oxidation time exceeds 10 h since more basic zinc sulfate is formed (Figure S30).…”
Section: Resultsmentioning
confidence: 86%
“…This process is similar to a self‐charging process while electrons migrate along the external circuit from the anode to the cathode to ensure electrical neutrality. [ 38 ] Based on the above analysis, the self‐charging performance of the KMO/C cathode was investigated. The GCD curves were first measured.…”
Section: Resultsmentioning
confidence: 99%
“…However, with the onset of self-charging process, Mn 3+ and Mn 4+ with higher valence states gradually appear and dominate (Figure 6c). [21,38] The mass concentrations of Zn 2+ and K + in the electrolyte before and after self-charging were also examined by ICP (Table S4, Supporting Information). As presented in Figure 6c, Zn ions are extracted at the same time as the valence of Mn increases, leading to an increase in the mass concentration of Zn 2+ in the electrolyte after self-charging.…”
Section: Self-charging Performance and Mechanism Of Kmo/cmentioning
confidence: 99%
“…As is well-known, different from sunlight, air is everywhere, and it can be used anytime and anywhere as a cost-free energy resource because chemical energy of oxygen in air can be changed into electrical energy by redox reaction. , Thus, an effective way to build a self-charging power system is to combine the chemical energy of oxygen with a rechargeable battery. In recent years, chemically self-charging AZIBs via O 2 in air (also named as air-rechargeable AZIBs) have been developed, and they are still in their infancy. For example, in 2020, Niu et al reported a chemically self-charging AZIB based on CaVO inorganic cathode, and the redox reaction between the discharged inorganic cathode (CaZn 3.6 VO) and O 2 is accompanied by the removal of Zn 2+ ions . Very recently, Niu et al also reported a chemically self-charging AZIB based on BQPH (benzo­[ i ]­benzo-[6,7]­quinoxalino­[2,3- a ]­benzo­[6,7]-quinoxalino­[2,3- c ]­phenazine-5,8,13,16,21,24-hexaone) organic cathode, in which the redox reaction between the discharged organic cathode and O 2 is accompanied by the removal of H + ions, but the two reported self-charging AZIBs display limited cycle stability (only four to five cycles).…”
Section: Introductionmentioning
confidence: 99%